Preliminary screening of crops for stimulation in population of Catenaria anguillulae Sorokin: facultative endoparasite of nematodes - and S.S. VAISH*, DURGAWATI PATEL, R.N. YADAV, P.K. DASH (Indian Phytopathology, 2016)
Population studies on C. anguillulae in rhizosphere of the different crops viz., pumpkin, cowpea, chilli, ridge gourd, maize, spinach, sorghum, bitter gourd, bottle gourd, black gram, green gram, sunflower, lady’s finger, tomato, brinjal, coriander, pigeonpea, pointed gourd, sponge gourd, onion, potato, chickpea, pea, sarson, carrot, radish, barley, garlic, lentil, bread wheat, fenugreek, berseem, sugar beet, rice and sesamum based on semiquantification methods using second stage juveniles of A. tritici revealed that most of the test crops increased population of the fungus. Pumpkin and linseed crops stimulated population of C. anguillulae more than twenty folds. Out of the test crops, chilli, cowpea, berseem, sugar beet, carrot, wheat, spinach and garlic showed ten folds increase in population of the fungus. Further, it was noticed that garlic which is a non-host crop for root knot nematode exhibited thirteen folds increase in population of C. anguillulae. Hence, after assessment at farmers’ fields, such crops have hope to incorporate into disease management module for integrated management of diseases caused by plant parasitic nematodes.